Depression, Healthcare Utilization, Missed Work, and Health Behaviors Among US Young Workers: Data From the 2015 National Health Interview Survey. Issue 10 (12th October 2021) - Leung, Cherry Y.; Lee, Soo-Jeong
Abstract : Objective: We examined the prevalence of depression and its impact on healthcare utilization, work absenteeism, and health behaviors among United States (US) young workers. Methods: Data of 1053 young workers (ages 18 to 25) from the 2015 US National Health Interview Survey were analyzed to examine these associations. Results: Seven percent of US young workers reported feeling often depressed (daily or weekly). Often depressed young workers had increased odds for healthcare provider visits, mental healthcare use, 1 to 2 emergency department visits, and 3 to 5 and more than or equal to 6 missed work days, smoking, and sleeping less than 7 hours. Conclusions: Our findings suggest that depressed young workers have increased needs for healthcare utilization and are at increased risk for missing work, smoking, and reduced sleep. Resources should be prioritized for depression screening and prevention programs at the workplace and healthcare settings.